2016
DOI: 10.3390/w8020047
|View full text |Cite
|
Sign up to set email alerts
|

Winter Irrigation Effects in Cotton Fields in Arid Inland Irrigated Areas in the North of the Tarim Basin, China

Abstract: Abstract:Winter irrigation is one of the water and salt management practices widely adopted in arid irrigated areas in the Tarim Basin located in the Xinjiang Uygur Autonomous Region in the People's Republic of China. A winter irrigation study was carried out from November 2013 to March 2014 in Korla City. A cotton field was divided into 18 plots with a size of 3 mˆ3 m and five winter irrigation treatments (1200 m 3 /ha, 1800 m 3 /ha, 2400 m 3 /ha, 3000 m 3 /ha, and 3600 m 3 /ha) and one non-irrigation as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…When the winter irrigation rate was greater than 3600 m 3 •hm −2 , the moisture content of soil layer 0-100 cm increased by more than 20% and the desalination exceeded 40%. This conclusion was consistent with the research results proposed by Zhang et al [33] that a winter irrigation rate of 3600 m 3 •hm −2 can provide a suitable water and salt environment for cotton seedling emergence in the following year, whereas Yang et al [17] proposed that the appropriate winter irrigation rate for cotton fields in southern Xinjiang should be 1800-3600 m 3 •hm −2 , and Li et al [34] indicated that the total irrigation rate should be within 3750 m 3 •hm −2 for the winter and spring irrigation in southern Xinjiang. The winter irrigation rate concluded from the present study was slightly higher than the optimal winter irrigation rate of 3000 m 3 •hm −2 for cotton fields in northern Xinjiang proposed by Chen et al [35] and Mou et al [16].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When the winter irrigation rate was greater than 3600 m 3 •hm −2 , the moisture content of soil layer 0-100 cm increased by more than 20% and the desalination exceeded 40%. This conclusion was consistent with the research results proposed by Zhang et al [33] that a winter irrigation rate of 3600 m 3 •hm −2 can provide a suitable water and salt environment for cotton seedling emergence in the following year, whereas Yang et al [17] proposed that the appropriate winter irrigation rate for cotton fields in southern Xinjiang should be 1800-3600 m 3 •hm −2 , and Li et al [34] indicated that the total irrigation rate should be within 3750 m 3 •hm −2 for the winter and spring irrigation in southern Xinjiang. The winter irrigation rate concluded from the present study was slightly higher than the optimal winter irrigation rate of 3000 m 3 •hm −2 for cotton fields in northern Xinjiang proposed by Chen et al [35] and Mou et al [16].…”
Section: Discussionsupporting
confidence: 93%
“…Mu et al [16] studied the effects of irrigation methods and winter irrigation rates on the soil water content, temperature, and salinity in cotton fields under drip irrigation in northern Xinjiang, and concluded that the effect on water content and salt leaching of a high rate of winter irrigation was particularly effective, with the optimum winter irrigation rate under drip irrigation mode being 3000 m 3 •hm −2 ; under these conditions, the impact of winter irrigation on soil water and salt concentration could reach a depth of 300 cm. Yang et al [17] demonstrated that, as the winter irrigation rate increased, the soil salt leaching effect was enhanced, but irrigation water-use efficiency was reduced, with the optimal winter irrigation rates on cotton fields in southern Xinjiang being 1800-3600 m 3 •hm −2 . Liu et al [18] applied winter irrigation to jujube (Ziziphus jujube) plantations in southern Xinjiang and reported that drip irrigation in winter at a rate of 3150 m 3 •hm −2 could significantly increase soil water content and salt leaching, increase the survival rate of the jujube trees the following year, and promote their growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [12] used a revised ENVIRO-GRO model to show that flood irrigation with a large amount of water after harvest can efficiently and significantly reduce salt accumulation within the top soil profile. Similarly, Yang et al [18] reported that winter irrigation is one of the water and salt management practices widely adopted in arid irrigated areas and that the strength of the desalination effect of winter irrigation increased with increasing water irrigation volume. Zhong et al [16] recommended that winter irrigation should be carried out when the ground begins to freeze at night but thaws during the day and reported that the beneficial effects of winter irrigation arise mainly from the washing away of salts, which decreases salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Soil moisture, especially soil water in the topsoil, is one of the controlling factors for hydrological, meteorological, and ecological processes [6]. The stability of soil moisture content, irrigation volumes, and the appropriate timing of irrigation are critical for developing effective agricultural water management practices and improving agricultural water use efficiency [7]. For winter wheat growth stages, there are different levels of sensitivity to water demands in the tillering, jointing, heading, milky dough, and harvest stages across the entire winter wheat growth season.…”
Section: Introductionmentioning
confidence: 99%